Dapoq Rush / Nur Adlin Abid Kamal - Abid Kamal, Nur Adlin (Universiti Teknologi MARA, Kedah, 2018)
Dapoq Rush is a smartphone game application, Want to be a real cook? Become a chef of your choice, discover new source ingredients, and unlock hundreds of redoes from all around Malaysia and win thorned kitchen battles! Battle by cooking foods ranging from main dish, dessert, to beverages. Enjoy variety of settings and cooking techniques.